2003
DOI: 10.1002/uog.89
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of isolated fetal intracardiac echogenic focus to trisomy 21 at the mid‐trimester sonogram in women younger than 35 years

Abstract: Objective To determine whether an isolated echogenic intracardiac focus in the fetal heart in the mid-trimester (16-24 weeks)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 20 publications
1
22
1
4
Order By: Relevance
“…Recent studies say that there is no increased risk of Down's syndrome in low-risk women with echogenic foci. 16,17 The risk of aneuploidy is not increased with isolated choroids plexus cyst. 3,9 However, the pregnant women detected to have choroid plexus cyst in the fetus were also informed that USG may not be able to detect all associated malformations, and rarely a fetus with isolated choroid plexus cyst may have chromosomal abnormality.…”
Section: Counselingmentioning
confidence: 99%
“…Recent studies say that there is no increased risk of Down's syndrome in low-risk women with echogenic foci. 16,17 The risk of aneuploidy is not increased with isolated choroids plexus cyst. 3,9 However, the pregnant women detected to have choroid plexus cyst in the fetus were also informed that USG may not be able to detect all associated malformations, and rarely a fetus with isolated choroid plexus cyst may have chromosomal abnormality.…”
Section: Counselingmentioning
confidence: 99%
“…In a recent study on 12,373 cases, 267 echogenic foci were diagnosed, 149 of them were isolated, there was no cases of T21 among any case of these with age < 35. 16 In an another prospective study, there were 12,672 cases included, 479 cases of EF were diagnosed, 90% were isolated, only one case had T21 (positive LH ratio of 2.66). This study concluded that amniocentesis is not warranted in low-risk cases with isolated EF.…”
Section: Originmentioning
confidence: 96%
“…In a recent study on 12,373 cases, 267 EFs were diagnosed, 149 of them were isolated, and there were no cases of T21 among women less than 35 years of age [4]. In an another prospective study of 12,672 women, 479 cases of EF were diagnosed, of which 90% were isolated with only one case of T21 (+LH ratio of 2.66).…”
Section: Introductionmentioning
confidence: 95%